Australian SME micro-offshoring opportunities in the Philippines: An expanding niche market? - Peter K. Ross (Philippine Institute for Development Studies (PIDS), 2016)
This paper examines how Filipino-based business process outsourcing centers have been developing services, including offshore "staff leasing" and "co-managed services" arrangements, that are helping to overcome traditional small and medium enterprise (SME) resource constraints. These "micro-offshoring" models greatly reduce transaction costs for Australian SMEs seeking to outsource/offshore former in-house work and appear to be supporting a rapid increase in the number of Australian-based SMEs offshoring professional services to the Philippines. Micro-offshoring further provides job opportunities for Filipino tertiary graduates and entrepreneurial opportunities for local Filipino SMEs looking to enter and tap this market. This research also suggests that it may encourage Australian SMEs to shift to more long-term offshoring models over time, such as local incorporation, and therefore foster foreign direct investment.
Keywords: 330; Philippines; micro-offshoring; outsourcing; BPO; Australian SMEs; staff leasing; co-managed services